การศึกษาการดำเนินการจัดกิจกรรมพัฒนาผู้เรียนสำหรับเด็กต่างด้าวในโรงเรียนต้นแบบคนพลัดถิ่น สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสมุทรสาคร - พลวัฒน์ ศลันธร; วิเศษศิริ ผศ.ดร. ปองสิน (An Online Journal of Education, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพและปัญหาการดำเนินการจัดกิจกรรมพัฒนาผู้เรียนสำหรับเด็กต่างด้าวในโรงเรียนต้นแบบคนพลัดถิ่น ตามกรอบการบริหาร ประกอบด้วย 1) การวางแผน 2) การดำเนินงาน 3) การประเมินผล และกรอบกิจกรรมพัฒนาผู้เรียน ประกอบด้วย 1) การแนะแนว 2) การกิจกรรมนักเรียน 3) กิจกรรมเพื่อสังคมและสาธารณประโยชน์ ประชากร คือ โรงเรียนต้นแบบคนพลัดถิ่น สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสมุทรสาคร ผู้ให้ข้อมูล ได้แก่ ผู้อำนวยการโรงเรียน และกลุ่มครูผู้รับผิดชอบการจัดกิจกรรมพัฒนาผู้เรียน เครื่องมือที่ใช้ในการวิจัย คือ แบบสัมภาษณ์ วิเคราะห์ข้อมูลโดยวิธีวิเคราะห์เนื้อหา ผลการวิจัย สภาพการดำเนินการจัดกิจกรรมพัฒนาผู้เรียน พบว่า 1) ด้านการวางแผนการจัดกิจกรรมพัฒนาผู้เรียน ผู้อำนวยการมีการประชุมชี้แจงทำความเข้าใจกับครูในการกำหนดระเบียบข้อบังคับ มีการกำหนดภาระหน้าที่ชัดเจน 2) ด้านการดำเนินงานจัดกิจกรรมพัฒนาผู้เรียน ครูมีการปฐมนิเทศนักเรียนก่อนการเข้าร่วมกิจกรรมเพื่อชี้แจงรายละเอียด 3) ด้านการประเมินผลการจัดกิจกรรมพัฒนาผู้เรียน มีการสรุปกิจกรรมเป็นรูปเล่มนำส่งฝ่ายบริหารปัญหาการดำเนินการจัดกิจกรรมพัฒนาผู้เรียน พบว่า 1) การวางแผนการจัดกิจกรรมพัฒนาผู้เรียน ด้าน การเตรียมบุคลากรพบปัญหามาก 2) ด้านการดำเนินงานจัดกิจกรรมพัฒนาผู้เรียน พบปัญหา คือ ด้านการติดตามดูแลการจัดกิจกรรม 3) ด้านการประเมินผลการจัดกิจกรรมพัฒนาผู้เรียน พบปัญหาเรื่องการรายงานผลการจัดกิจกรรม The objectives of this research was to study the state and the problems of the student development activities organizing for immigrant students in diaspora school master according to the management frameworks (1.Planning 2.Implementation 3.Evaluation) and the developments of the activity framework (1.Counseling activities 2.student activities 3.Social and Welfare activities) The population was diaspora school master Samutsakhon primary educational service area office. The sample groups are school director and student development activity teachers. The tool of this research was the interviewing. Data were analyzed by content analysis. The results of the state of student development activity planning were 1) The planning of the activities were conducted by School director in arranging meeting to clarify the activities procedures and individual duties to teachers. 2) The implementation of student development activity was the student orientation arranged by teachers before participating in activities 3) The evaluation of student development activity was the conclusion of activities were compiled in books and submitted to the management. The problems of the student activities procedures were 1) The planning of the activities was found in the preparation of the officers. 2) The implementation of the student activities was found in the follow up of the activities organizing 3) The evaluation of the student activities was found in the activities results reports.